(untitled) - Willoughby, Dawn (Chichester, 2015)
An Essential Guide to Business Statistics offers a clear and concise introduction for business students studying statistics for the first time. It helps them to become proficient in using statistical techniques and interpreting their results within a business content and will enable them to have a better understanding of customers, decision making and planning for the future.
Keywords: Commercial statistics,Thống kê thương mại